Exploring attitudes towards reading through a multimodal approach: Students’ conative attitudes perspective - Maharani, Mega Mulianing; Fitriati, Sri Wuli; Faridi, Abdurrachman; Rukmini, Dwi (Universitas Islam Sultan Agung, 2025)
There has to be a new way of thinking about reading in this technological age. This approach is called a multimodal approach. It is an approach that contributes to several modes in the reading sources. To explore students' attitudes towards reading through a multimodal approach in terms of their conative attitudes’ perception, this study employs this approach. This study used a descriptive quantitative method to fulfill the purpose. Fifteen students were purposively selected as the sample. They had the same characteristics, such as having completed the previous reading class. Ten steps were involved in conducting the study. The data were collected using a closed-ended questionnaire. A statistical analysis using SPSS was performed on the collected data. According to the numbers, four out of the eight categories are significantly high, accounting for 46.7%. It can be concluded that students have a pleasant impression. The statements made by the students demonstrate that they remained focused on reading through the channel informed by the teacher, participated in class, avoided procrastination with classmates, and engaged in reading. It can be concluded that based on the quantitative data, the students’ conative attitude perception towards the implementation of the multimodal approach in their reading class is positive.